Analysis and Development of Information Security Framework for Distributed E-Procurement System - Sugianto Sugianto (Proceeding of the Electrical Engineering Computer Science and Informatics, 2019)
This paper proposes an information security framework for distributed E-Procurement system in Indonesia. E-Procurement in Indonesia has been implemented since 2008, and has provided many benefits. However, there are also information security issues in the use of IT. Developing an information security program is needed to overcome the issues. We compare and analyze the LPSE and ISO 27001 Standards to develop framework. The results show there are some gaps between LPSE Standard and ISO 27001. By implementing the proposed framework, LPSE as a provider of distributed EProcurement system can be easier to implement the LPSE and ISO 27001 Standards simultaneously as an obligation to comply with government regulations